[Mn(CO)(3)(bpy)(N-2-chlorobenzylbenzimidazole)] OTf complex as a new photoactivatable CO-releasing molecule - Ustun, E.; Dusunceli, S. Demir; Ozdemir, I. (2017)
Metal carbonyl complexes have been accepted major for storage and transportation of carbon monoxide which is an important gasotransmitter. We synthesized novel manganese(I) carbonyl complex with general formula [Mn(CO)(3)(bpy)L] OTf (bpy = 2,2'-bipyridyl, L= N-(2-chlorobenzyl) benzimidazole, OTf = SO3CF3). The complex was characterized by LC-MS, H-1 NMR, 2D-COSY NMR, C-13 NMR, IR and elemental analysis. The CO-releasing properties of the complex were investigated. The DFT/TDDFT analyses were also made by ORCA package program.